THE ROLE OF FEMALE POETS IN THE HISTORY OF UZBEK LITERATURE - Kamolova Saodat Rahimjonovna (Modern American Journals, 2025)
This article discusses some of the outstanding representatives of female poets in the history of Uzbek literature — Nodira, Uvaysiy, and Mahzuna. In the 18th–19th centuries, through their creative works, they made a significant contribution to enriching Uzbek classical poetry and became subjects of discussion and interpretation throughout their era and beyond. Their poetry vividly reflects their artistic thinking, inner emotions, social status, and their unique perspective on noble values such as love, loyalty, and humanism. The article emphasizes their individual creative directions and the aesthetic traditions they established in Uzbek literature.
Keywords: Nodira, Uvaysiy, Mahzuna, Uzbek classical poetry, female poets, lyrical love poetry, moral and spiritual interpretation, riddles.